2016
DOI: 10.1186/s12906-016-1312-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary randomised controlled study of short-term Antrodia cinnamomea treatment combined with chemotherapy for patients with advanced cancer

Abstract: BackgroundAntrodia cinnamomea (AC) is a popular medicinal mushroom in Taiwan that has been widely used for treatment of various cancers. Few clinical studies have reported its application and efficiency in therapeutic chemotherapy strategies. We performed a double-blind, randomized clinical study to investigate whether AC given for 30 days had acceptable safety and efficacy in advanced cancer patients receiving chemotherapy.MethodsPatients with advanced and/or metastatic adenocarcinoma, performance status (PS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 37 publications
(40 reference statements)
1
38
0
Order By: Relevance
“…A large variety of cancer entities, studied sample sizes, outcomes, treatment durations and observation times were seen ( Table 1). The medicinal mushrooms investigated were Agaricus sylvaticus (two trials) (Fortes et al, 2008;Costa Fortes et al, 2010;Costa Fortes and Carvalho Garbi Novaes, 2011;Valadares et al, 2013), Agaricus blazei murill (two trials) (Ahn et al, 2004;Tangen et al, 2015), Antrodia cinnamomea (one trial) (Tsai et al, 2016), Coriolus versicolor (one trial) (Chay et al, 2017) and Ganoderma lucidum (three trials) (Gao et al, 2003a;Oka et al, 2010;Zhao et al, 2012). All mushrooms were administered orally.…”
Section: Resultsmentioning
confidence: 99%
“…A large variety of cancer entities, studied sample sizes, outcomes, treatment durations and observation times were seen ( Table 1). The medicinal mushrooms investigated were Agaricus sylvaticus (two trials) (Fortes et al, 2008;Costa Fortes et al, 2010;Costa Fortes and Carvalho Garbi Novaes, 2011;Valadares et al, 2013), Agaricus blazei murill (two trials) (Ahn et al, 2004;Tangen et al, 2015), Antrodia cinnamomea (one trial) (Tsai et al, 2016), Coriolus versicolor (one trial) (Chay et al, 2017) and Ganoderma lucidum (three trials) (Gao et al, 2003a;Oka et al, 2010;Zhao et al, 2012). All mushrooms were administered orally.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigations have already shown the synergistic effects of EEA combined with cisplatin (16), sorafenib (12), and tamoxifen (13). The antitumor effect of EEA has been confirmed in a randomized controlled study, although the synergistic effects of EEA combined with chemotherapy were not observed (26). It has been proposed that cancer stem-like cells were involved in tumor initiation and occurrence of chemoradiotherapy resistance, responsible for compromised clinical outcomes of conventional therapies (2,27,28).…”
Section: Discussionmentioning
confidence: 95%
“…After taking AC for three months, there was no significant change in liver and renal function indices, blood pressure, triglyceride, and fasting blood glucose levels [ 7 ]. AC has been used in the complementary treatment of cancers, with some clinical test results reported, including colorectal cancer [ 8 ], adenocarcinomas [ 9 ], and lung cancer [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%